2016
DOI: 10.1111/hae.13019
|View full text |Cite
|
Sign up to set email alerts
|

Modelling lifelong effects of different prophylactic treatment strategies for severe haemophilia A

Abstract: Background: Lifelong prophylactic replacement therapy with clotting factor concentrates is recommended for severe haemophilia. The prophylactic dose determines both clinical outcome and treatment cost. In the absence of clinical studies, computer simulation was used to explore lifelong effects and clotting factor consumption for various prophylactic dose levels, and optimize strategies for switching between prophylactic and on-demand treatment. Design and Methods: Individual patients' lifetime joint bleeds, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although the direct clinical relevance of radiological joint changes is limited, its association with HRQoL is highly relevant, especially in the context of choosing the intensity of prophylactic treatment; should the aim be to prevent all bleeding or can a limited number of joint bleeds be accepted . In addition, it corroborates the observation that HRQoL is impacted by joint disease, rather than treatment received .…”
Section: Discussionmentioning
confidence: 65%
“…Although the direct clinical relevance of radiological joint changes is limited, its association with HRQoL is highly relevant, especially in the context of choosing the intensity of prophylactic treatment; should the aim be to prevent all bleeding or can a limited number of joint bleeds be accepted . In addition, it corroborates the observation that HRQoL is impacted by joint disease, rather than treatment received .…”
Section: Discussionmentioning
confidence: 65%
“…26 Extended throughout a lifetime, mean cumulative use is calculated to reach 19 Â 10 6 IU (vs 3.9 Â 10 6 IU for on demand treatment), with diminishing cost effectiveness. 26 The authors suggest that this model may provide some rationale for severe hemophilia A adults evolving from primary prophylaxis to a treatment plan that switches between nonprimary prophylaxis and on demand regimens based on rates of breakthrough hemorrhage and acceptable target levels of musculoskeletal bleeding protection, as well as both availability and cost of clotting factor. 26 And yet, the trends point to greater adoption of primary prophylaxis beyond childhood.…”
Section: Primary Prophylaxis Amentioning
confidence: 99%
“…26 The authors suggest that this model may provide some rationale for severe hemophilia A adults evolving from primary prophylaxis to a treatment plan that switches between nonprimary prophylaxis and on demand regimens based on rates of breakthrough hemorrhage and acceptable target levels of musculoskeletal bleeding protection, as well as both availability and cost of clotting factor. 26 And yet, the trends point to greater adoption of primary prophylaxis beyond childhood. The United Kingdom Haemophilia Centre Directors Organization (UKHCDO) national guidelines recommend continuing primary prevention into adulthood for all except the mildest bleeding phenotypes.…”
Section: Primary Prophylaxis Amentioning
confidence: 99%
“…The economic evaluation studies on the cost-utility (CU) of the PR versus OD conducted throughout the world have achieved a wide range of results. The results of some studies have shown that the use of PR reduces joint bleeding and has more cost-effectiveness(CE) and CU than OD [16,17]. It is also estimated that the use of PR can reduce the demand for some health care sources in addition to reducing the bleeding and secondary degenerative orthopedic changes and improving the health-related quality of life [18].…”
Section: Introductionmentioning
confidence: 99%